Penguatan Kompetensi Profesionalisme Guru pada Era Digital di SMP Taman Siswa - Aina Mulia Rizky; Amalia Apriliani; Devi Syalwa Putri; Faiz Muhammad Zacky; Joya Urmila Lubis; Samiullah Putra Limbong; Jamaludin Jamaludin; Sri Yunita (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
In the digital era, the role of teachers is not limited to teaching in the classroom but also as agents of change in shaping students' character and culture. This study employs a qualitative method, producing descriptive data in the form of written or spoken words from observed subjects. The primary objective of this research is to understand the importance of teacher professionalism in addressing the challenges of globalization and modernization. Based on the analysis, teachers at SMP Taman Siswa need to master four core competencies: pedagogical, personal, professional, and social. Additionally, proficiency in technology and the implementation of innovative learning methods, such as problem-based learning and project-based learning, are essential for enhancing learning effectiveness. The findings indicate that with the right approach, teachers can help students develop 21st-century skills, including critical thinking, creativity, collaboration, and communication.